Hexafluorophosphate additive enables durable seawater oxidation at ampere-level current density - Xun He; Yongchao Yao; Limei Zhang; Hefeng Wang; Hong Tang; Wenlong Jiang; Yuchun Ren; Jue Nan; Yongsong Luo; Tongwei Wu; Fengming Luo; Bo Tang; et al. (Nature Communications)
Abstract Direct seawater electrolysis at ampere-level current densities, powered by coastal/offshore renewables, is an attractive avenue for sustainable hydrogen production but is undermined by chloride-induced anode degradation. Here we demonstrate the use of hexafluorophosphate (PF₆⁻) as an electrolyte additive to overcome this limitation, achieving prolonged operation for over 5,000 hours at 1 A cm−2 and 2300 hours at 2 A cm−2 using NiFe layered double hydroxide (LDH) as anode. Together with the experimental findings, PF₆⁻ can intercalate into LDH interlayers and adsorb onto the electrode surface under an applied electric field, blocking Cl⁻ and stabilizing Fe to prevent segregation. The constant-potential molecular dynamics simulations further reveal the accumulation of high surface concentrations of PF6 − on the electrode surface that can effectively exclude Cl−, mitigating corrosion. Our work showcases synchronous interlayer and surface engineering by single non-oxygen anion species to enable Cl− rejection and marks a crucial step forward in seawater electrolysis.